Dynamic Response Analysis of Buried Drainage Pipes for Polymer Grouting Trenchless Rehabilitation under the Traveling Wave Effect - Fengyang Miao; Weiguo Li; Jianguo Xu; Zhihao Chen; Xiaoyu Feng (Advances in Civil Engineering)
The polymer grouting nonexcavation repair technology has been widely used in the repair of underground pipeline leaks, but the seismic response to the polymer repair pipeline is currently using a consistent excitation of seismic input without considering the influence of the traveling wave effect. This paper establishes the longitudinal and transverse vibration models of the polymer grout repair pipeline considering the traveling wave effect based on the elastic foundation beam theory. The seismic input uses artificially generated random seismic waves and solves the differential equations for pipeline vibration to carry out seismic response analysis of long-buried pipelines under three conditions: normal, vacant, and polymer grouting repair. The results show that after considering the traveling wave effect, the reaction of each measuring point on the pipeline has obvious phase characteristics, and the waveform of the distant measuring point has an obvious hysteresis phenomenon; the seismic wave velocity has a great influence on the deformation of the pipeline, and the displacement amplitude of the pipeline increases with the increase of the seismic wave velocity. The peak of pipeline displacement after vacancy will increase by 100%∼300% more than normal, while the difference in pipeline deformation after high polymer grouting is about 25% compared with normal, which means that the bottom vacant will have a great influence on pipeline deformation, and high polymer repair can restore the pipeline mechanical properties to normal levels.